IMPLEMENTATION OF INQUIRY LEARNING IN ENGLISH LEARNING TO INCREASE THE LEARNING ACTIVITY OF GRADE VII STUDENTS OF TAHFIDZ DARUL QUR'AN JUNIOR HIGH SCHOOL - Rohmatul Hidayah rahma; Tiyas Saputri (EDUPEDIA Publisher, 2026)
Purpose – This study aims to investigate the implementation of the Inquiry Learning model in improving the learning activeness of seventh-grade students in English learning at Tahfidz Darul Qur'an Junior High School. The study was conducted based on the low participation and passive learning behavior of students during English classes. Methodology – This research employed a qualitative descriptive approach using a case study design. The participants consisted of one English teacher and eight seventh-grade students selected purposively based on their level of learning activeness. Data were collected through participatory observation, semi-structured interviews, and documentation studies. The research procedures included classroom observation during the implementation of Inquiry Learning, interviews with teachers and students, and analysis of learning documents and reflection journals. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, including data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and technique triangulation. Findings – The findings revealed that before the implementation of Inquiry Learning, students tended to be passive, lacked confidence, and rarely participated in classroom discussions. After the implementation, students showed significant improvement in learning activeness, including increased participation, confidence in asking questions, involvement in group discussions, and oral communication skills in English. The Inquiry Learning stages successfully created a more interactive and student-centered learning environment. The study concludes that Inquiry Learning effectively enhances students’ learning activeness and motivation in English learning. Novelty – This study provides originality by exploring the implementation of Inquiry Learning qualitatively in a tahfidz-based junior high school context, which has rarely been investigated in previous studies. Significance – The findings of this study are beneficial for English teachers, researchers, and educational institutions, especially Islamic boarding school-based schools, in developing active and student-centered learning strategies.